Effect of Low-calorie Diet Supplemented with Genistein on Lipid Profile, Blood Glucose and Proinflammatory Biomarkers in Diet-induced Obese Rats - Hossein Rafiei; Fatemeh Haidari; Majid Karandish; Kosar Omidian; Majid Mohammad Shahi (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Background and Objective: Obesity is a worldwide public health problem that results in comorbidities including diabetes, dyslipidemia, coronary artery disease and some types of cancer. It seems that soy isoflavones can improve obesity and reverse subsequent metabolic disorders. In this study, we assessed the effect of restriction of calorie supplemented with genistein on diet-induced obese rats. Subjects and Methods: Thirty rats obesed with high fat diet were divided randomly into 3 experimental groups (n=10) as follows: group 1: low calorie diet supplemented with 50mg/kgbw genistein, group2: low calorie diet supplemented with Dimethyl Sulphoxide (DMSO) (as vehicle) and group3: obese control rats with ad libitum access to standard food. After 4 weeks, fasting blood samples were collected and analyzed for biochemical analysis. Results: The results showed that administration of genistein in conjunction with low calorie diet can synergistically improve triglyceride (p=0.005), VLDL (p=0.005), total cholesterol(p=0.002) and LDL-C (P=0.003) and increase HDL-C (p=0.001) but has no effect on body weight and proinflammatory biomarkers (resistin and CRP). Restriction of calorie also resulted in the decrease of glucose level, TG, TC, LDL, proinflammatory biomarker (CRP) and increase in HDL-C (p<0.05) but has no effect on resistin level.Conclusion: It seems that administration of genistein with restriction of calorie is useful for improvement of hyperlipidemia in obese hyperlipidemic patients.